Euro Area Policies : 2012 Article IV Consultation: Selected Issues Paper. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2012)
This 2012 Article IV Consultation-Selected Issues Paper on Euro Area Policies argues that the creation of a common eurozone financial stability architecture is an immediate priority to restore the viability of the Economic and Monetary Union. The paper presents a narrative of the various stages of the banking and sovereign crisis since the Summer of 2011. It also characterizes the downward spirals at play in periphery euro area countries and describes the process of financial de-integration within the euro area.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet